Improving Students' Writing Skills: Strategies and Practices of a Georgia Elementary School - Todd, Michael Robert (My University, 2019)
Writing has been a documented problem in American schools for more than 30 years. The purpose of this study was to identify the strategies and practices teachers in one Georgia elementary school used to significantly improve student writing scores as measured by the Georgia Milestones standardized test. This qualitative case study examined teachers’ life and career experiences, school-wide strategies related to writing, and classroom-based writing practices. Data collection included memos, interviews, teacher observations, and artifacts. Categorical aggregation was used to analyze the data. This study resulted in several major findings. All participants’ pedagogical approaches to writing instruction were influenced by their past experiences. All participants reported that the support from their school principals helped them settle on various practices leading to their success in teaching writing. All participants found formulaic writing strategies to be useful in improving students’ writing. Participants reported increased student learning when modeling was used as an instructional strategy.
I. INTRODUCTION 1 -- Problem Statement 3 -- Purpose Statement 3 -- Research Questions 3 -- Significance 4 -- Personal Background 4 -- Current Gap and Purpose 6 -- Causes and Consequences 6 -- Conceptual Framework 7 -- Methodology 9 -- Limitations 10 -- Definition of Terms 11 -- Chapter Summary 15 -- II. LITERATURE REVIEW 17 -- Problem Statement 17 -- Purpose 17 -- Research Questions 17 -- Significance 18 -- Conceptual Framework 18 -- Methodology 19 -- Description of the Problem 21 -- Writing Standards 25 -- Standardized Tests 26 -- Writing Assessments 26 -- Work Implications for Future College Students 27 -- Writing in College and Workplace 27 -- Reasons for Poor Writing Scores 30 -- Teachers Are Unprepared to Teach Writing 31 -- Teacher Efficacy 32 -- Time to Teach Writing 34 -- NCLB’s Lack of Emphasis on Writing 35 -- The Challenge of Grading Writing 36 -- Lack of Resources to Teach Writing 37 -- Efforts to Improve Writing 37 -- Writing in Common Core State Standards 40 -- Best Writing Practices 41 -- Teachers’ Experiences As Writers 43 -- How Teachers Were Taught As Writers 43 -- Teacher’s Writing for Personal Use 45 -- School-wide Strategies to Improve Student Writing 45 -- Classroom-based Writing Practices 46 -- Students Writing Competency 46 -- Formulaic Writing 47 -- Chapter Summary 47 -- III. METHODOLOGY 49 -- Researcher Design and Rationale 50 -- Setting 52 -- Role of the Researcher 55 -- Methodology 56 -- Participant Selection 56 -- Self-Inventory 57 -- Data Collection 58 -- Focus Group 58 -- Individual Interviews 60 -- Observations 63 -- Data Analysis 65 -- Issues of Trustworthiness 67 -- Credibility 67 -- Dependability 68 -- Transferability 69 -- Confirmability 69 -- Ethical Procedures 70 -- Chapter Summary 71 -- IV. PARTICIPANT DESCRIPTIONS 73 -- Participant Requirements 73 -- Physical Site Description 74 -- Participant Narratives 76 -- Deborah 77 -- Jay 81 -- Linda 86 -- Sally 90 -- Sarah 93 -- Stella 97 -- Stephanie 100 -- Chapter Summary 103 -- V. RESULTS 105 -- Purpose Statement 105 -- Research Questions 106 -- Participant Requirements and School Demographics 106 -- Data Analysis 107 -- Phase 1: Preparing for Coding 109 -- Phase 2: Coding the Data 110 -- Phase 3: Grouping Codes 113 -- Phase 4: Identifying Correspondence in Patterns 115 -- Phase 5: Recognizing Larger Patterns 115 -- Major Themes 116 -- Teachers’ Experiences on Classroom Practices 117 -- Leadership Attention 121 -- Modeling as a Roadmap to Success 124 -- Quieting the Noise through Formulaic Writing 127 -- Summary of Themes 131 -- VI. Conclusions, Implications, and Recommendations 132 -- Research Questions: Final Discussions Summary 134 -- Life and Career Experiences of Teachers 134 -- School-wide Strategies for Writing Instruction 138 -- Classroom-based Practices for Writing Instruction 140 -- Intersection of Research Questions 151 -- Implications and Discussion of the Study 152 -- Impact of Teachers’ Experiences on Classroom Practices 154 -- Impact of Leadership Focus 156 -- Impact of Modeling as a Roadmap to Success 157 -- Impact of Quieting the Noise through Formulaic Writing 158 -- Suggestions for Further Improvement 158 -- Develop a Writing Committee 159 -- Re-implement Writing Across the Curriculum 160 -- Fine-Tune Modeling Practices 160 -- Limitations of the Study 161 -- Recommendations for Further Study 163 -- Final Conclusions 165 -- REFERENCES 168 -- APPENDIX A: IRB APPROVAL 193 -- APPENDIX B: FOCUS GROUP PROTOCOL 195 -- APPENDIX C: INTERVIEW PROTOCOL 197 APPENDIX D: INTERVIEW QUESTIONS 196 APPENDIX E: VARIETY OF INSTRUCTIONAL METHODS 199 APPENDIX F: SURVEY QUESTIONS 206.
Keywords: Dissertations, Academic--United States; Writing; Learning strategies; Education, Elementary; Educational tests and measurements--Standards; Georgia